Analysis of the properties of RFSSW lap joints of Alclad 7075-T6 aluminum alloy sheets under static and dynamic loads - Kubit, Andrzej; Faes, Koen; Jurczak, Wojciech; Bucior, Magdalena; Kluz, Rafał (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2020)
This paper presents research regarding refill friction stir spot welding (RFSSW) of EN AW-7075-T6 Alclad aluminium alloy sheets, and the joint behaviour under static and dynamic loads. Single-point lap joint of sheets with different thicknesses, which corresponds to those used in aircraft fuselage structures, i.e. upper sheets with a thickness of 1.6 mm and lower sheets with a thickness of 0.8 mm, were analysed regarding the failure mechanism in static shear testing. It has been shown that a properly made joint is destroyed as a result of tension in the lower plate. The lower plate at the edge of the weld is structurally weakened by the HAZ, but also geometrically due to plastic deformation during the welding process, which has been demonstrated by metallographic investigations as well as by the FEM numerical model. Single-row RFSSW welded joints with different spacing of the welds and a riveted joint were impact tested. It has been shown that welded joints are characterized by a greater stiffness, which is higher when the spacing of the welds is smaller. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)